IMPLEMENTATION OF ACCOUNTING STANDARDS FROM THE PERSPECTIVE OF MICRO, SMALL AND MEDIUM ENTERPRISES - Nasrah, Hidayati; Ratna, Ikhwani (Faculty of Economics and Business University of Mataram, 2024)
This study explores the implementation of the Financial Accounting Standard of Micro, Small, and Medium Enterprises (FAS MSMEs), focusing on gaps in the financial reporting of MSMEs and the challenges faced by MSMEs. Qualitative descriptive methods analyze reporting habits, constraints, and understanding of MSME actors towards FAS MSME. The results show that many MSME actors have not adopted this standard due to limited knowledge, human resources, and awareness of the importance of accurate reporting. These conditions hinder financial transparency and access to formal financial services. This study suggests interventions such as training programs to improve financial reporting capacity and emphasizing the importance of MSME actors' awareness of accounting practices and professional support for compliance.